Deteminação da atividade protetiva dos inibidores de corrosão. I. Métodos não-eletroquímicos - Giannetti, Biagio Fernando; Sumodjo, Paulo Teng-An; Benedetti, Assis Vicente; Centellas, Francesc; Cabot, Pere Lluis; Garrido, José António; Pérez, Ernesto (Eclética Química, 1992)
.